Perilaku Ibu Tentang Imunisasi Dasar Pada Bayi Berusia 0-12 Bulan Di Puskesmas Glugur Kota Medan - HELMIWATI, HELMIWATI; HARTONO, ADI; SOPIANA, ANA (Universitas Teknokrat Indonesia, 2024)
The degree of child health is one of the health indicators of a nation and is usually measured through child mortality rates, immunization coverage and other parameters. Based on data from the Ministry of Health in Indonesia in 2015, the percentage of complete basic achievement in Indonesia was 86.54%. This figure has not yet reached the 2015 target of 91%, while for North Sumatra province, complete basic immunization coverage in 2015 only reached 79.9%. Behavior is a response or reaction of a person to a stimulus (stimulus from outside), perila occurs through a process of stimulus to the organism, then the organism responds